Use of ATP-Binding Cassette Subfamily A Member 13 (ABCA13) for Sensitive Detection of Focal Pathological Forms of Subclinical Bovine Paratuberculosis - Blanco-Vázquez, Cristina; Alonso-Hearn, Marta; Iglesias, Natalia; Vázquez, Patricia; Juste, Ramón A.; Garrido, Joseba M.; Balseiro, Ana; Canive, María; Amado, Javier; Queipo, Manuel A.; Iglesias, Tania; Casais, Rosa (Frontiers in Veterinary Science, 2022)
Bovine paratuberculosis (PTB) is a chronic enteritis caused by Mycobacterium avium subspecies paratuberculosis (Map) with a heavy economic impact worldwide. Map infected animals can remain asymptomatic for years while transmitting the mycobacteria to other members of the herd. Therefore, accurate detection of subclinically infected animals is crucial for disease control. In a previous RNA-Seq study, we identified several mRNAs that were overexpressed in whole blood of cows with different PTB-associated histological lesions compared with control animals without visible lesions. The proteins encoded by two of these mRNAs, ATP binding cassette subfamily A member 13 (ABCA13) and Matrix Metallopeptidase 8 (MMP8) were significantly overexpressed in whole blood of animals with focal histological lesions, the most frequent pathological form in the subclinical stages of the disease. In the current study, the potential as sensitive early diagnostic tools of commercial ELISAs based on the detection of these two biomarkers was evaluated in serum samples of 704 Holstein Friesian cows (566 infected animals and 138 control animals from PTB-free farms). For this evaluation, infected animals were classified according to the type of histological lesions present in their gut tissues into three groups: focal (n=447), multifocal (n=59) and diffuse (n=60). The ELISA based on the detection of ABCA13 was successfully validated showing good discriminatory power between animals with focal lesions and control animals (sensitivity 82.99% and specificity 80.43%). However, the MMP8-based ELISA showed a poor discriminatory power between the different histological groups and non-infected controls. The ABCA13-based ELISA showed a higher diagnostic value (0.822) than the IDEXX ELISA (0.517), the fecal bacterial isolation (0.523) and the real-time PCR (0.531) for the detection of animals with focal lesions. Overall, our results indicate that this ABCA13 ELISA greatly improves the identification of subclinically infected animals with focal lesions that are undetectable using current diagnostic methods.